A Comparision of Laboratory Diagnostic Methods of Tuberculosis and Aetiology of Suspected Cases of Pulmonary Tuberculosis (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2015)
Introduction: Tuberculosis remains a worldwide public health problem despite the highly effective drugs and vaccines are available making tuberculosis a preventable and curable disease. The objective of this study was to compare the different laboratory diagnostic methods of tuberculosis and determine its prevalence. Methodology: Morning sputum samples were collected from suspected cases of pulmonary tuberculosis and preceded for Ziehl Neelsen staining, fluorescent staining (auramin-O) and mycobacterium culture in Lowenstein Jensen medium. Results: Total 78 suspected cases of pulmonary tuberculosis were included in this study among them 53 were male and 25 were female. Out of 78 cases, 46 cases were found to be culture positive. In culture positive cases (83%) were found to be M. tuberculosis and (17%) were found to be slow grower, fine colonies, AFB positive but niacin test negative (mycobacteria other than M. tuberculosis). In the direct microscopic examination by Ziehl Neelsen stained smear 26 samples were found to be acid fast bacilli and one sample was culture negative but acid fast bacilli positive. In fluorescent stained smear 34 samples were found to be positive for acid fast bacilli and 5 samples were culture negative but acid fast bacilli positive. Culture was accepted as gold standard, the sensitivity of direct microscopic examination was found 56.5% for Ziehl Neelsen staining and 73.9% for fluorescent staining respectively. Conclusion: In culture positive cases M. tuberculosis and mycobacteria other than M. tuberculosis was found to be 83% and 17% respectively, it was found higher in male than female. Fluorescent microscopy is superior to Ziehl Neelsen microscopy but gives more false positive result than Z-N staining. Combining of Ziehl Neelsen and fluorescent staining is better than fluorescent staining alone.DOI: http://dx.doi.org/10.3126/saarctb.v11i2.12427  SAARC J TUBER LUNG DIS HIV/AIDS, 2014;XI(2), page: 1-6